Educational Potentials of Flipped Learning in Intercultural Education as a Transversal Resource in Adolescents - Fuentes Cabrera, Arturo (Religions, 2020)
The evolution of technology in the educational field has resulted in the emergence of new ways of teaching and learning, adapted to the formative characteristics of a digital era. This is the case of Flipped Learning (FL), an innovative teaching methodology that uses technology to carry out instructional action and change learning moments and spaces. The objective of this study is to verify the effectiveness of FL on a traditional methodology without the use of digital resources in teaching content related to intercultural education. A quantitative research method has been followed by an experimental design. Two study groups have been set up. With the control group a traditional training methodology has been used, and with the experimental group an innovative one, through FL. A total of 60 students of the 4th level of Secondary Education from an educational center in Ceuta (Spain) have participated. An ad hoc questionnaire derived from other validated instruments has been used for data collection. The findings show that the FL has achieved better results in the different dimensions analyzed. Therefore, it is concluded that the implementation of innovative training actions such as FL can obtain better results in academic indicators than a traditional methodology.